Impacts of climate change on surface ozone and intercontinental ozone pollution: A multi-model study - Doherty, R. M.; Wild, O.; Shindell, D. T.; Zeng, G.; MacKenzie, I. A.; Collins, W. J.; Fiore, A. M.; Stevenson, D. S.; Dentener, F. J.; Schultz, M. G.; Hess, P.; Derwent, R. G.; et al. (Journal of geophysical research. Atmospheres, 2013)
The impact of climate change between 2000 and 2095 SRES A2 climates on surface ozone (O)3 and on O3 source‐receptor (S‐R) relationships is quantified using three coupled climate‐chemistry models (CCMs). The CCMs exhibit considerable variability in the spatial extent and location of surface O3 increases that occur within parts of high NOx emission source regions (up to 6 ppbv in the annual average and up to 14 ppbv in the season of maximum O3). In these source regions, all three CCMs show a positive relationship between surface O3 change and temperature change. Sensitivity simulations show that a combination of three individual chemical processes—(i) enhanced PAN decomposition, (ii) higher water vapor concentrations, and (iii) enhanced isoprene emission—largely reproduces the global spatial pattern of annual‐mean surface O3 response due to climate change (R2 = 0.52). Changes in climate are found to exert a stronger control on the annual‐mean surface O3 response through changes in climate‐sensitive O3 chemistry than through changes in transport as evaluated from idealized CO‐like tracer concentrations. All three CCMs exhibit a similar spatial pattern of annual‐mean surface O3 change to 20% regional O3 precursor emission reductions under future climate compared to the same emission reductions applied under present‐day climate. The surface O3 response to emission reductions is larger over the source region and smaller downwind in the future than under present‐day conditions. All three CCMs show areas within Europe where regional emission reductions larger than 20% are required to compensate climate change impacts on annual‐mean surface O3. Key Points Climate change impacts on surface O3 are reproduced by three key processesO3 response driven by changes in O3 chemistry rather than changes in transportFuture O3 response to emission changes larger near source but smaller downwind